2015
DOI: 10.1021/acs.analchem.5b00116
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Solvent Based Methods for Molecular Characterization of Soil Organic Matter by High-Resolution Mass Spectrometry

Abstract: Soil organic matter (SOM), a complex, heterogeneous mixture of above and belowground plant litter and animal and microbial residues at various degrees of decomposition, is a key reservoir for carbon (C) and nutrient biogeochemical cycling in soil based ecosystems. A limited understanding of the molecular composition of SOM limits the ability to routinely decipher chemical processes within soil and accurately predict how terrestrial carbon fluxes will respond to changing climatic conditions and land use. To elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 22 publications
7
176
0
Order By: Relevance
“…The detailed instrument parameters and analysis procedures, optimized during dissolved organic matter experiments, have been described previously (Kujawinski and Behn, 2006;Minor et al, 2012;Tfaily et al, 2015). A standard Bruker electrospray ionization (ESI) source was used to generate negatively charged molecular ions to target analysis of oxidized organic compounds.…”
Section: Esi-fticr-ms Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed instrument parameters and analysis procedures, optimized during dissolved organic matter experiments, have been described previously (Kujawinski and Behn, 2006;Minor et al, 2012;Tfaily et al, 2015). A standard Bruker electrospray ionization (ESI) source was used to generate negatively charged molecular ions to target analysis of oxidized organic compounds.…”
Section: Esi-fticr-ms Analysismentioning
confidence: 99%
“…In addition, observations of likely dinitroaromatics during all air mass influences, potentially from aqueous nitration of nitroaromatic compounds, have important implications because of their light-absorbing and mutagenic properties (Purohit and Basu, 2000;Zhang et al, 2011Zhang et al, , 2013. During wildfire influence, the cloud water showed evidence of aqueous SOA formation, including oligomer formation involving methylglyoxal Yasmeen et al, 2010) and aqueousphase reactions of syringol and guaiacol (Yu et al, 2014(Yu et al, , 2016. Monoterpene-derived organosulfates and organonitrates (Surratt et al, 2008) were observed in the cloud water during all air mass influences, similar to previous cloud water studies (Boone et al, 2015;Pratt et al, 2013).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the mechanical separation of the material from the columns (Figure 2, 2. Mechanical separation), samples of bulk substrate (BS) and rhizospheric material (RS) were extracted in either water (Optima ® LC/MS grade, Fisher Scientific, Suwanee, GA, USA) or 100% methanol (Optima ® HPLC grade, Fisher Scientific, Suwanee, GA, USA) according to Tfaily et al [34] as follows: 0.5 g of BS or RS were weighed and divided evenly for water and methanol extraction, then mixed and shaken for 5 minutes. For RS, root samples were dipped in the solvent, manually stirred and gently shaken for 5 minutes, to minimize the portions of cut roots to be extracted in water or methanol.…”
Section: Fourier Transform Ion Cyclotron Resonance Mass Spectrometry mentioning
confidence: 99%
“…We anticipated that (a) microbes would contribute to the new SOM pool by stabilizing root exudates and producing complex refractory C compounds. With our recent development of a solvent-based method for molecular SOM characterization by high resolution mass spectrometry [34], we also expected that (b) microbial residues will leave a stable signature of persistent OM on mineral surfaces that remain attached following a series of extractions with different polarity solvents. Furthermore, we hypothesized that (c) SOM composition would differ between rhizosphere soil and bulk soil.…”
Section: Introductionmentioning
confidence: 99%